Digitalization challenges in education during COVID-19: A systematic review - Wong, Sing Yun (Informa UK Limited, 2023)
The global outbreak of the COVID-19 pandemic crisis has led to the disruption of the learning activities of many educational institutions across the world. The transition from conventional education learning to digital learning has left both educators and students in the face of challenges. The impact of education loss was found to be more critical for students from poor and rural backgrounds. The shift of education activities to online teaching and learning has aroused growing interest in studies examining the impact of the global outbreak on the education sector. Although there had been studies in the past that have provided a literature review on the impact of the COVID-19 pandemic on teaching and learning, however, systematic review using the PRISMA approach on this particular study of interest has remained relatively less. Hence, this study aimed at conducting a systematic review by adopting the PRISMA strategy to focus on the challenges faced by the education sector during the crisis period. The results from this review found 82 articles by keywords search. Through a systematic review, the literature is extensively scanned to answer the well-defined research questions and four (4) main themes have been developed with 19 articles included in the finding synthesizing. The review conducted in this paper will contribute by providing comprehensive reviews of the past literature done specifically in examining the challenges to digitalization in learning during the pandemic crisis.